The impacts of miscategorization & the effects of “Project dclattering” towards customers’ point of view - Raisa, Tasneem Zaman (Brac University, 2023)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.